IMPORTANCE OF DEVELOPING AUTOMATED INFORMATION SYSTEMS AND MOBILE APPLICATIONS (Web of Teachers: Inderscience Research, 2024)
This article examines the practical importance of speed reading programs. The need for these software applications today has been examined, and among them, it has been determined which areas are most in need of speed learning programs. Among the speed reading programs, software applications adapted for remote language learning are currently more active. Such software applications are many and varied, and differ from each other in terms of language learning time, ease of use, and the number of languages they cover. Among them, Duolingo, a software application created for language learning, was reviewed in more detail and its achievements and shortcomings were explained.